Analisis Pengendalian Mutu pada Pengolahan Ikan Pelagis Beku di PT Perikanan Nusantara (Persero) Cabang Benoa Bali - DEVI, KADEK PUTRI TRISNA; SUAMBA, I KETUT; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Quality Control Analysis on Frozen Pelagic Fish Processing PT Perikanan Nusantara (Persero) Branch Benoa Bali PT Perikanan Nusantara (Persero) Branch Benoa Bali since 1972, has implemented a quality control. But in reality, there is pelagic fish damage in 2014 with a percentage of 2.74%. The aim of this research are determining the implementation of quality control at frozen pelagic fish processing and quality control systems using statistical quality control approach with controlling map and quality cost.Results of this research is the implementation of quality control in processing frozen pelagic fish viewed from good manufacturing practices meets the standards of the company, it is evidenced by the statement of the customer. When monitoring using the map control, quality control that occurs has not been implemented properly, because of a lot of damaged fish are out of the control limits. Quality control using quality cost that implemented by the company is still loose, because the real quality cost incurred for quality control cost are  48,801,869 IDR, quality assurance fee of 441,122,00 IDR, and the total cost for the quality of 489,923,869 IDR with the level of damage 40,102 kg, it is greater than the should quality cost with 146,727,587 IDR for quality control cost, quality assurance fee of 147,718,000 IDR, and the total cost for the quality level  is 293,445,587 IDR with level of damage 13,338 kg. Thus, companies need to increase intensively on ship handling and processing as well as quality control. Keywords: frozen pelagic fish, quality control, statistical quality control